Application of Utopia and Graxpert AI in Studying Celestial Objects to Support Research and Education Interests at the High School Level, and Public Outreach - Iwan Maryawan; Robiatul Muztaba; Herpratiwi; Sowiyah; Melya Riniarti; Ririn Andriyani; Aditya Abdillah Yusuf (Jurnal Penelitian Pendidikan IPA, 2026)
UTOPIA is a remotely operated robotic telescope developed by Observatorium Astronomi Itera Lampung (OAIL) to support astronomy education and research. Integrated with an Android-based control system, it enables remote observations and is applied across different levels of astronomy education. This study integrates UTOPIA with GraXpert, an open-source artificial intelligence tool for astronomical image enhancement through background extraction and noise reduction. A program involving 30 senior high school students was conducted through guided celestial observations, data acquisition, and collaborative image analysis. Participants were introduced to optical telescope principles, CCD imaging, and basic astronomical data processing, while GraXpert was used to enhance nebular image quality and visualization. The effectiveness of the program was evaluated using pre-test and post-test assessments. Results show a significant increase in understanding, with the mean score rising from 10.33 to 25.10 and a normalized gain of 0.75, indicating high conceptual improvement. Questionnaire results indicate positive learning perception, with most participants reporting improved understanding of nebular objects and better comprehension of the UTOPIA system, reflected in dominant positive responses. These findings demonstrate that integrating robotic telescopes with AI-based image processing supports astronomy education and improves students’ conceptual understanding through inquiry-based activities.